The laplacian spectral radius of a class of bipartite graphs - Xuezhong, Tan; Liu, Bolian (Utilitas Mathematica, 2012)
The Laplacian spectral radius of a graph G is defined to be the greatest eigenvalue of the Laplacian matrix of G. Let B(n, n - k) be the class of graphs of bipartite graphs of order n with n - k pendant vertices. In this paper, the graphs with maximal Laplacian spectral radius in B(n, n - k) are determined. MSC: 05C50.